Investigation of Gene Expression and DNA Methylation From Seven Different Brain Regions of a Crab-Eating Monkey as Determined by RNA-Seq and Whole-Genome Bisulfite Sequencing - Lim, Won-Jun; Kim, Kyoung Hyoun; Kim, Jae-Yoon; Kim, Hee-Jin; Kim, Mirang; Park, Jong-Lyul; Yoon, Seokjoo; Oh, Jung-Hwa; Cho, Jae-Woo; Kim, Yong Sung; Kim, Namshin (Frontiers in Genetics, 2019)
The crab-eating monkey is widely used in biomedical research for pharmacological experiments. Epigenetic regulation in the brain regions of primates involves complex patterns of DNA methylation. Previous studies of methylated CpG-binding domains using microarray technology or peak identification of sequence reads mostly focused on developmental stages or disease, rather than normal brains. To identify correlations between gene expression and DNA methylation levels that may be related to transcriptional regulation, we generated RNA-seq and whole-genome bisulfite sequencing data from seven different brain regions from a single crab-eating monkey. We identified 92 genes whose expression levels were significantly correlated, positively or negatively, with DNA methylation levels. Among them, 11 genes exhibited brain region-specific characteristics, and their expression patterns were strongly correlated with DNA methylation level. Nine genes (SLC2A5, MCM5, DRAM1, TTC12, DHX40, COR01A, LRAT, FLVCR2, and PTER) had effects on brain and eye function and development, and two (LHX6 and MEST) were previously identified as genes in which DNA methylation levels change significantly in the promoter region, and are therefore considered brain epigenetic markers. Furthermore, we characterized DNA methylation of repetitive elements at the whole genome through repeat annotation at single-base resolution. Our results reveal the diverse roles of DNA methylation at single-base resolution throughout the genome, and reflect the epigenetic variations in adult brain tissues.